Impact of the Magnitude and Timing of Fluid Overload on Outcomes in Critically Ill Children: A Report From the Multicenter International Assessment of Worldwide Acute Kidney Injury, Renal Angina, and Epidemiology (AWARE) Study - Selewski, David T; Gist, Katja M; Basu, Rajit K; Goldstein, Stuart L; Zappitelli, Michael; Soranno, Danielle E; Mammen, Cherry; Sutherland, Scott M; Askenazi, David J; Ricci, Zaccaria; Akcan-Arikan, Ayse; Gorga, Stephen M; et al. (Critical care medicine, 2023)
With the recognition that fluid overload (FO) has a detrimental impact on critically ill children, the critical care nephrology community has focused on identifying clinically meaningful targets for intervention. The current study aims to evaluate the epidemiology and outcomes associated with FO in an international multicenter cohort of critically ill children. The current study also aims to evaluate the association of FO at predetermined clinically relevant thresholds and time points (FO ≥ 5% and FO ≥ 10% at the end of ICU days 1 and 2) with outcomes. Prospective cohort study. Multicenter, international collaborative of 32 pediatric ICUs. A total of 5,079 children and young adults admitted consecutively to pediatric ICUs as part of the Assessment of the Worldwide Acute Kidney Injury, Renal Angina and Epidemiology Study. None. The FO thresholds at the time points of interest occurred commonly in the cohort (FO ≥ 5%Day1 in 38.1% [ n = 1753], FO ≥ 10%Day1 in 11.7% [ n = 537], FO ≥ 5%Day2 in 53.3% [ n = 1,539], FO ≥ 10%Day2 in 25.1% [ n = 724]). On Day1, multivariable modeling demonstrated that FO ≥ 5% was associated with fewer ICU-free days, and FO ≥ 10% was associated with higher mortality and fewer ICU and ventilator-free days. On multivariable modeling, FO-peak, Day2 FO ≥ 5%, and Day2 FO ≥ 10% were associated with higher mortality and fewer ICU and ventilator-free days. This study found that mild-to-moderate FO as early as at the end of ICU Day1 is associated with adverse outcomes. The current study fills an important void in the literature by identifying critical combinations of FO timing and quantity associated with adverse outcomes (FO ≥ 5%Day1, FO ≥10%Day1, FO ≥ 5%Day2, and FO ≥ 10%Day2). Those novel findings will help guide the development of interventional strategies and trials targeting the treatment and prevention of clinically relevant FO.